2021
DOI: 10.3390/antibiotics10101172
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fitness Cost Caused by Tigecycline-Resistance Gene tet(X6) in Different Host Bacteria

Abstract: The emergence and prevalence of the tet(X) gene and its variants in the environment and in clinical settings constitute a growing concern for public health worldwide. Accordingly, the tigecycline resistance gene variant tet(X6) is widely detected in Proteus spp. and Acinetobacter spp. rather than Enterobacteriaceae, while the underpinning behind this phenomenon is still unclear. To investigate the mechanisms underlying this distinct phenomenon, we assessed the fitness of the engineered plasmid pBAD-tet(X6) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This sharp contrast implied that the high-level expression of tet (X4) may arise biosynthetic burden for host bacteria. Previous study has demonstrated the expression of tet (X6) exerted high fitness cost in E. coli as well ( Jiang et al, 2021 ), suggesting the expression of tet (X) variants may be positively correlated with fitness cost. Second, an elevated conjugation frequency was observed in both evolved strains, and the expression of genes involving in the conjugative process was increased as well.…”
Section: Discussionmentioning
confidence: 99%
“…This sharp contrast implied that the high-level expression of tet (X4) may arise biosynthetic burden for host bacteria. Previous study has demonstrated the expression of tet (X6) exerted high fitness cost in E. coli as well ( Jiang et al, 2021 ), suggesting the expression of tet (X) variants may be positively correlated with fitness cost. Second, an elevated conjugation frequency was observed in both evolved strains, and the expression of genes involving in the conjugative process was increased as well.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, 31 a competition experiment of the strains was carried out. Briefly, the mixed bacterial liquid of NO.22 and NO.22R (1:1) was cultured under the above conditions, and cultured bacteria were sucked at 0, 4, 8, 12, 24, and 48 h. The CFU of the culture solution was counted on an agar plate and an agar plate containing 1 × MIC fosfomycin for 24 h. Fitness was calculated using a competition experiment, and the relative fitness (W) of the mutant to wild type was calculated as follows:…”
Section: Methodsmentioning
confidence: 99%
“…pneumoniae harboring mobile tmexCD1-toprJ isolated from microbial enumerations of hospitalized patients have been reported ( Sun S. et al, 2020 ; He et al, 2021 ; Qin et al, 2021 ; Yang et al, 2021 ; Liu et al, 2022 ), particularly recovered from diverse ecological niches from different world regions ( Tables 1 , 3 ). Additionally, the presence of VAGs in the MTR gene-bearing strains could confer a fitness advantage to the organisms ( Jiang et al, 2021 ).…”
Section: Distribution Reservoirs and Traits Of Mobile Tigecycline Res...mentioning
confidence: 99%